Jean-Marie Delavay (1834-1895), His Botanical Collection in Yunnan and Relationship with the National Museum of Natural History at the End of the Nineteenth Century: Cooperation, Interactions, and Contributions - Li, Guoqiang (Annali di Ca’ Foscari: Serie Orientale)
Jean-Marie Delavay (1834‑1895), a missionary of the Missions étrangères de Paris, was one of the most influential botanical collectors in Yunnan and China. He sent his collection to the Muséum national d’histoire naturelle, where Adrien Franchet (1834‑1900) identified the specimens. This article examines Delavay’s collection in Yunnan and the scientific collaboration between Delavay and the Museum, based on seventy-three of his letters and other archives. It highlights the cooperation between the French state, religious orders, and scientific institutions in the nineteenth century, which contributed to advancements in the natural sciences.